Keefektifan Pembelajaran Daring di SMP Negeri 1 Trenggalek - Imam Asrori; Rufii Rufii; Harwanto Harwanto (Journal on Education, 2023)
This study has the objectives, namely: to identify and describe the planning, implementation, evaluation, supporting factors, inhibiting factors and efforts that can be made in overcoming learning obstacles in SMP Negeri 1 Trenggalek. This research is a qualitative research, in which the data collection techniques used are questionnaires, observations, interviews and documentation. The data sources from this study were 35 students and 2 teachers who were respondents in this study. Based on the results of the research, it was found that planning for the use of online learning was carried out by the teacher by pouring it into the lesson plan. Implementation of the use of online learning at SMP Negeri 1 Trenggalek could be carried out properly in management by the teacher, positive student responses and activities. Evaluation of the use of online learning explained that learning that is carried out runs effectively with an increase in the average value of report cards which has increased from semester to semester. Factors supporting courageous learning are the presence of young teachers who are technologically literate and familiar with network technology and the support of parents with provision of the required facilities, the inhibiting factor for the use of courageous learning is the unstable internet network and the facilities owned by students are insufficient and the efforts that can be made by the teacher are to optimize the use of multiple ime dia like video, audio, CD-ROM based and utilize applications that require a minimal internet network.